Analysis of anthropogenic transformation of the hydrographic network in the northern part of Lviv according to cartographic sources - Ye. Іvanov; O. Pylypovych (Екологічна безпека та збалансоване ресурсокористування)
The emergence of new and densification of existing urban spaces in Lviv leads to anthropogenic transformation of the hydrographic network. The purpose of the study was to analyse the degree of transformation of water objects in the northern part of the city based on cartographic sources. The study covered the northern part of Lviv, the town of Dublyany, the villages of Malekhiv, Velyki Hrybovychi, Zbyranka and Murovane. The study of water bodies was carried out with topographic maps of the scale range from 1:25,000 to 1:100,000, which made it possible to cover a time period of more than 240 years. Clear trends to decrease the length of open channels, the number of tributaries and the water content of the Holoskivskyy, Zboivskyy and Malekhivskyy streams, which is due to both natural and anthropogenic factors had been marked. The length of the natural channel of the Holoskivskyy stream decreased from 4.7 to 0.9 km, the Zboivskyy stream ‒ from 5.2 to 3.2 km, and the Malekhivskyy stream ‒ from 7.9 to 5.3 km. The largest number of ponds (15 units; 10.3 hectares) on streams was found in the second half of the 18th century. Subsequently, a decrease in both the number and area of ponds was observed. The lowest figures fall on the interwar Polish period, when only four ponds with a total area of 2.5 hectares were recorded. During the Soviet period, the number and area of ponds increased slightly (9 units; 4.6 hectares) and reached the level that existed in the second half of the 19th century. There were 14 water mills operating on most of the ponds of that time located in the villages of Holosko Velyke, Zamarstyniv, Zboyishcha and Malekhiv. After that, the number of mills steadily decreased: at the beginning of the 19th century ‒ nine; in the second half of the 19th century ‒ seven; in the interwar period – five. After the World War II, the operation of all water mills was stopped. The conducted analysis of the degree of transformation of the hydrographic network is aimed at correcting the development plan of the northern part of the city and implementing the environmental management system